A legal study on the crime of infanticide in Malaysia / Ungku Masmera Ungku Farouk ...[et al.] - Ungku Farouk, Ungku Masmera; Zainuddin, Nur Hidayah; Mustafa, Nur Ajeerah; Azmi, Nor Hamiza (2011)
Nowadays, the problem of infanticide or killing of a new-born babies is a major concern in our country. Eventhough there are several provisions available to regulate this problem, yet there are still cases regarding infanticide on the rise. The psychosocial factors and the flaws in the existing law regarding infanticide are two main contributory factors that lead to this problem. In Malaysia, the provisions on infanticide are available in Penal Code which are Section 3 09A and Section 309B for the offence of infanticide and Section 318 for the concealment of the dead body of the babies. However, there are several flaws in these sections that render the implimentation of the law to be less efficient. Besides that, most of the countries have their own laws regarding the offence of infanticide, for example, the Infanticide Act 1938 in United Kingdom, and in Canada the provisions regarding this offence are available in the Criminal Code of Canada. Therefore, this study will highlights the causes of infanticide, the existing laws together with the flaws in it. It also higlights the similarities and the differences between the laws in Malaysia, United Kingdom and Canada. This study provides some suggestions to improve the existing laws regarding infanticide in Malaysia.